Eficiência de utilização da lisina para codornas de corte em crescimento - VIEIRA FILHO, Francisco das Chagas (2019)
Quails have favorable characteristics for their production, however, its creation is still facing difficulties, although in recent years have significant increase in productivity due to the introduction in specific quail for slaughter. For these birds to express their potential is necessary a good nutrition, but it is essential to obtain adequate estimates of lysine requirements as it is one of the most important amino acids for birds. These requirements can be determined using factorial models, which require parameters such as the efficiency of lysine utilization for their elaboration. However, studies that have determined these efficiencies for meat quail are non-existent. Therefore, the objective was to estimate the efficiency of lysine utilization for the growth of male and female meat quail from 21 to 35 days of age. A total of 500 21-day-old quails of both sexes with an average initial weight of 119.23 ± 1.92 g were used. The birds were randomly distributed in a 5 x 2 factorial design (digestible lysine level x sex), with five replications per treatment. The birds were fed rations containing 0.714; 0.816; 0.918; 1.020 and, 1.122% digestible lysine. Final weight (FW; g/bird); feed intake (FI; g/bird/day); digestible lysine intake (LysI; mg/bird/day); feather weight (FW; g/bird); feather free body protein deposition (FFBPD; mg/bird/day); feather protein deposition (FPD; mg/bird/day) and, protein deposition in the body as a whole (BPD; mg/bird/day); feather free body lysine deposition (FFBLysD; mg/bird/day), feather lysine deposition (FLysD; mg/bird/day), and lysine deposition in the body as a whole (BLysD; mg/bird/day), feather free body fat deposition (FFBFD; mg/bird/day), feather fat deposition (FFD; mg/bird/day), and fat deposition in the body as a whole (BFD; mg/bird/day) were assessed. The variables were regressed as a function of LysI in each sex, and the individual equations of each sex were compared by parallelism tests, using sex as the categorical variable and LysI as the covariate. This procedure allowed the estimation of the efficiency of lysine utilization in the feather free body and in the body as a whole, through the coefficients “b1” of the equations. A multiple regression without intercept was also used in an attempt to estimate the efficiencies of lysine utilization for feather free body depositions and feathers individually. To compare the efficiencies of lysine utilization for feather free body lysine deposition, obtained by the different methods, the t-statistic was used. There was no interaction between lysine level and sex in any of the evaluated variables. Sex effect on FFBFD was observed (P=0.0374) and BFD (P=0.0469), with females showing higher depositions compared to males corresponding to 26.23 and 25.91%, respectively. There was no sex effect (P>0.05) for FFBLysD, and the average common efficiency for both sexes was 48%. By the multiple linear regression method the DLysCD was 44.6%. Since the efficiency of lysine use for carcass deposition determined by the simple linear regression method did not differ from the multiple linear regression method (P>0.05), the best estimate of the lysine deposition efficiency was 46.3%. The efficiency of lysine utilization for deposition in the feather free body and quail feathers were 46.3 and 18.1%, respectively, no differences between males and females.